-1+49x=21x+43

Simple and best practice solution for -1+49x=21x+43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1+49x=21x+43 equation:


Simplifying
-1 + 49x = 21x + 43

Reorder the terms:
-1 + 49x = 43 + 21x

Solving
-1 + 49x = 43 + 21x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21x' to each side of the equation.
-1 + 49x + -21x = 43 + 21x + -21x

Combine like terms: 49x + -21x = 28x
-1 + 28x = 43 + 21x + -21x

Combine like terms: 21x + -21x = 0
-1 + 28x = 43 + 0
-1 + 28x = 43

Add '1' to each side of the equation.
-1 + 1 + 28x = 43 + 1

Combine like terms: -1 + 1 = 0
0 + 28x = 43 + 1
28x = 43 + 1

Combine like terms: 43 + 1 = 44
28x = 44

Divide each side by '28'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| 1/2*2+13=9 | | 9.2(+6.4)=132.48 | | t+13=18 | | -5q+9=-4q | | y=6*x | | x^2+(y^2)+z^2=z | | 5+2(x-3)=8+7 | | q-6=8 | | 18-5x=12-7x | | 2sin(x)tan(x)=3 | | 4x-3y-12z= | | 28y-1=5 | | 5-4y=8 | | 4x^3+4x-4=0 | | 7y-11-10y+3= | | 25+0.05n=7+0.11n | | 4x^3+4x=4 | | 647=6x-99.4 | | 5x-7=4x+36 | | 12g-(-7)=31 | | 5x+32=8x-13 | | m-16=6 | | 5=-x+5 | | -1.5f+24=10.50 | | 2x+3=9+2 | | 4y+(2-2)=7-2 | | 8x+14= | | 3(4x+4)-9= | | 3+4x=-15+x | | 2x+2=82 | | 7n+5n=2n+7 | | (5x+8)(5x-9)= |

Equations solver categories